Distribusi Spasial Anemon dan Ikan Anemon di Perairan Kelurahan Malalayang Dua, Manado - Aldi Pengan; Ari Berty Rondonuwu; Alex Denny Kambey (Sam Ratulangi University, 2012)
DISTRIBUSI SPASIAL ANEMON DAN IKAN ANEMON DI PERAIRAN KELURAHAN MALALAYANG 2 MANADO1 Â Aldi Pengan, Ari B Rondonuwu, Alex D Kambey Â ABSTRACT Â This study was conducted in front of coastal villages Malalayang 2. Performed data acquisition at the date of September 16 and October 6, 2011. Located at 1o27'42.2